The effect of cryoprotectant on the viability and motility of goldfish Carassius aurtus sperm after 48 hours refrigerated - Nurlaili Nurlaili; Itsnatani Salma; Kartini Eriani; Siti Maulida; Zainal Abidin Muchlisin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
The principle of sperm preservation is to prolong the viability of spermatozoa by reducing the degree of metabolism during storage at low temperatures, and one method involved was a cryoprotectant as a sperm protector. This study aimed to determine the best type of cryoprotectant for refrigeration storage of goldfish Carrasius auratus sperm. A completely randomized design was used, and five types of cryoprotectant were tested, namely Methanol, Ethanol, Ethylene Glycol, Glycerol, and DMSO at a 10% concentration combined with 15% egg yolks. The sperm was diluted with Ringer’s solution and stored at 4⁰C for 48 hours. The ANOVA test revealed that cryoprotectant significantly affected the motility and viability of sperm after 48 hours of refrigeration (P0.05). The results showed that 10% DMSO combined with 15% egg yolk could maintain sperm motility and viability better than other treatments, with values of 85.80% and 86.50%, respectively, which were significantly different from the other treatments. Glycerol produced the second-best sperm quality with motility and viability values of 71.13% and 74.13%, respectively. Therefore, DMSO is the most effective cryoprotectant for refrigeration storage of goldfish sperm.